Study of energy efficiency opportunities in UTHM - Noranai, Zamri (2008)
Sustainable energy usage has been recognized as one of the important measure to increase the competitiveness of the nation globally. Many strong emphases were given in the Ninth Malaysia Plan (RMK9) to improve energy efficient especially to government buildings. With this in view, a project to investigate the potential of energy saving in selected building in Universiti Tun Hussein Onn Malaysia (UTHM) was carried out. In this project, a case study involving electric energy consumption of the academic staff office building was conducted. The scope of the study include to identify energy consumption in a selected building, to study energy saving opportunities, to analyse cost investment in term of economic and to identify users attitude with respect to energy usage. The MS1525:2001, Malaysian Standard -Code of practice on energy efficiency and use of renewable energy for non-residential buildings was used as reference. Several energy efficient measures were considered and their merits and priority were compared. Improving human behavior can reduce energy consumption by 6% while technical measure can reduce energy consumption by 44%. Two economic analysis evaluation methods were applied; they are the payback period method and net present value method.